WAIST-HIP RATIO, BODY MASS INDEX, AND COGNITIVE DECLINE IN OLDER PUERTO RICANS. (11th November 2018) - Crowe, M; Dávila-Roman, A; Barba, C; Downer, B; Andel, R
Abstract: Similar to many areas in the mainland U.S., Puerto Rico has also experienced growing rates of overweight and obesity. We examined two commonly used anthropometric measures of weight status, waist-hip ratio (WHR) and body mass index (BMI), in relation to cognitive performance and cognitive decline in a population-based sample of older adults in Puerto Rico. Participants included 3, 662 community-dwelling adults age 60+ from the Puerto Rican Elderly: Health Conditions (PREHCO) Study. Measures of height, weight, waist circumference, and hip circumference were taken in participants' homes at baseline. Average age of the sample was 71.4 years old. Cognitive function was measured at baseline and four years later using the Minimental Cabán (MMC), a previously validated Spanish-language instrument. We examined bivariate correlations between these measures at baseline as well as covariate-adjusted regression models with cognitive decline as an outcome. At baseline, although WHR and BMI were positively correlated with each other (r=0.12, p<.001), higher WHR was negatively associated with cognition (r=-0.07, p<.001), and higher BMI was positively associated with cognitive performance (r=0.10, p<.001). In a regression model adjusted for age, gender, education, depressive symptoms, and diabetes, higher WHR was associated with greater cognitive decline (β=.04, p<.05) and higher BMI was associated with less cognitive decline (β=-.04, p<.05). Our findings suggest that higher WHR, but not BMI, may be associated with adverse cognitive outcomes in older Puerto Ricans.